Frontline Contact Aspiration Treatment for Emergent Large Vessel Occlusion: A Review Focused on Practical Techniques - Dong-Hun Kang; Yang-Ha Hwang (Journal of Stroke, 2019)
Endovascular thrombectomy (EVT) as the standard care for acute stroke due to large vessel occlusion has recently been validated through several randomized controlled trials (RCTs). Contact aspiration (CA) and stent retriever (SR) are the two major EVT methods currently used. Because the RCTs have mostly evaluated SR devices, there was a demand to test CA in relation to SR as a frontline EVT treatment method. Recently, the Contact Aspiration vs Stent Retriever for Successful Recanalization (ASTER) study, the first RCT to compare CA and SR, demonstrated similar efficacy between them as a frontline EVT for patients with large vessel occlusions. This facilitates further investigation to confirm better frontline EVT for patients with acute stroke. In this review, we discuss past and recent developments in CA techniques, focusing on related literature. Additionally, we describe practical skills to overcome technical difficulties that can be encountered during the CA procedure. Finally, we review the evolution of device technologies, including a newer version of using a large-bore aspiration catheter.